The Roles of Marital Dissolution and Subsequent Repartnering on Loneliness in Later Life. (26th September 2019) - Wright, Matthew R; Hammersmith, Anna M; Brown, Susan L; Lin, I-Fen
Abstract: Objectives: Loneliness in later life is associated with poorer health and higher risk of mortality. Our study assesses whether gray divorced adults report higher levels of loneliness than the widowed and whether social support or repartnership offset loneliness. Method: Using data from the 2010 and 2012 Health and Retirement Study, we estimated ordinary least squares regression models for women ( n = 2, 362) and men ( n = 1, 127) to examine differences in loneliness by dissolution pathway (i.e., divorce versus widowhood), accounting for social support and repartnership. Results: Divorced men were lonelier than their widowed counterparts. Although social support reduced loneliness among men, the difference between the divorced and widowed persisted. Repartnership assuaged men's loneliness and reduced the variation between divorced and widowed men. Among women, the results did not reveal differences in loneliness for the divorced and widowed although social support and repartnership linked to less loneliness. Discussion: Later-life marital dissolutions increasingly occur through divorce rather than spousal death. Some older adults go on to form new partnerships. Our findings demonstrate the importance of gerontological research widening the lens beyond widowhood to consider the ramifications of later-life divorce and repartnership for well-being.